Explore RE - Clarke, Steve; Hayes, Jan; Parry, Lesley (Dynamic learning, 2019)
Engage students with religion, philosophy and ethics at Key Stage 3 and encourage them to develop the skills they need to succeed at GCSE. This accessible Student Book is designed to provide a firm foundation for the reformed GCSE specifications, while still allowing you to teach a broad and balanced KS3 curriculum. - Easily introduce a new scheme of work for KS3 with this cost-effective, single-book course that provides 120 ready-made lessons that can be used flexibly over a 2-year or 3-year KS3 - Teach KS3 RE with confidence whatever your level of expertise; this structured course is ready to pick up and teach whether you are an RE specialist or new to teaching the subject - Capture your students' interest with engaging lessons and activities that will encourage them to pursue Religious Education at GCSE - Lay the groundwork for GCSE, equipping your students with a solid grasp of the six major world religions, as well as the core philosophical and ethical issues - Test knowledge and understanding with regular formative assessments that enable students to keep track of their progress throughout the course - Prepare your students for assessment at GCSE, with practice questions for each lesson designed to build the confidence, understanding and evaluative skills needed for GCSE success.